1996
DOI: 10.1136/bjsm.30.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of iron metabolism indices and their relation with physical work capacity in athletes.

Abstract: Objective-To evaluate the relation between iron status and physical working capacity, and to assess the effect of oral iron treatment on these variables, in athletes with borderline iron status. Methods-Blood haemoglobin (Hb), packed cell volume (PCV), red blood cell count (RBC), serum iron, total iron binding capacity (TIBC), and ferritin determinations were compared in 71 male and 18 female athletes participating in various sports and in matched male (n = 11) and female (n =8) controls. The first aim was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
2
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 26 publications
0
13
2
1
Order By: Relevance
“…On the one hand, the following authors found increases in ferritin levels: Kang and Matsuo [23] used 40 mg of elemental iron per day for 4 weeks in elite-category female soccer players; Hinton and Sinclair [24] administered a supplement of 30 mg of iron sulfate·per day for 6 weeks to athletes of both sexes; and Gropper et al [22] supplemented female students with 160 mg of ferrous sulfate·per day (50 mg of elemental iron) for 5 weeks. On the other hand, Tsalis et al [13], who administered 40 mg of ferrous sulfate for 6 months to young swimmers of both sexes, and others reported in the Nielsen and Nachtigall review [8] did not found this effect; however, using 56 mg·day −1 for 3 weeks has been reported to produce significant increases in serum ferritin [31]. In relation to the minimum time to observe effects in iron metabolism parameters in non-anemic athletes, Nielsen and Nachtigall [8] have suggested that the required period is 3 weeks [8], although the time of supplementation reported in different papers is highly variable.…”
Section: Discussionmentioning
confidence: 93%
“…On the one hand, the following authors found increases in ferritin levels: Kang and Matsuo [23] used 40 mg of elemental iron per day for 4 weeks in elite-category female soccer players; Hinton and Sinclair [24] administered a supplement of 30 mg of iron sulfate·per day for 6 weeks to athletes of both sexes; and Gropper et al [22] supplemented female students with 160 mg of ferrous sulfate·per day (50 mg of elemental iron) for 5 weeks. On the other hand, Tsalis et al [13], who administered 40 mg of ferrous sulfate for 6 months to young swimmers of both sexes, and others reported in the Nielsen and Nachtigall review [8] did not found this effect; however, using 56 mg·day −1 for 3 weeks has been reported to produce significant increases in serum ferritin [31]. In relation to the minimum time to observe effects in iron metabolism parameters in non-anemic athletes, Nielsen and Nachtigall [8] have suggested that the required period is 3 weeks [8], although the time of supplementation reported in different papers is highly variable.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies carried out in athletic horses showed that physical exercise of different intensities and durations influence iron homeostasis (Mills et al 1996;Karamizrak et al 1996;Inoue et al 2005;Scoppetta et al 2012). It is noteworthy that iron depletion could influence athletic performance through low haemoglobin concentration with a consequent reduction in the oxygen transport capacity, decreasing the maximal oxygen uptake (Walker et al 2001).…”
mentioning
confidence: 99%
“…Dietary iron interventions using a cereal product offer an alternative way of improving dietary iron intake 44 . The relation between iron status and physical working capacity was evaluated, and the effect of oral iron treatment on these variables, in athletes with borderline iron status was assessed 45 . The results of the study showed Hb, serum iron, serum ferritin, and transferrin saturation increased with iron treatment in both males (P < 0.01) and females (P < 0.05).…”
Section: Impact Of Supplementation On Biochemical Parametersmentioning
confidence: 99%